2007
DOI: 10.1063/1.2760143
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-power dependence of catastrophic optical damage in AlGaInP laser diodes

Abstract: Facet temperature changes in broad-area red-emitting high-power AlGaInP lasers are analyzed by means of micro-Raman spectroscopy. Measurements as a function of injection current demonstrate that the temperature at the laser output facet rises linearly with optical output power. Temperature profile measurements across the laser stripe show a strong correlation between near field intensity, facet temperature, and catastrophic optical damage (COD). Additionally, temperature-power analyses reveal that a critical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In this respect, a slow current sweep is equivalent to a cw experiment. Figure 4a shows the results of such measurements for a homogeneous set of red-emitting devices as reported by BouSanayeh [73]. The abrupt power fall-offs which are marked by arrows, clearly point to the COD thresholds P COD .…”
Section: Cod Threshold In Cw Operationmentioning
confidence: 96%
See 1 more Smart Citation
“…In this respect, a slow current sweep is equivalent to a cw experiment. Figure 4a shows the results of such measurements for a homogeneous set of red-emitting devices as reported by BouSanayeh [73]. The abrupt power fall-offs which are marked by arrows, clearly point to the COD thresholds P COD .…”
Section: Cod Threshold In Cw Operationmentioning
confidence: 96%
“…At a heat-sink temperature of 40°C, one observes the so-called thermal rollover instead of COD. This behavior illustrates that the critical facet temperature [73,74], i. e., T facet = T bulk +ΔT :…”
Section: Cod Threshold In Cw Operationmentioning
confidence: 99%
“…2b it is worthwhile noticed that the temperature of COD seeds has a sudden increase of about 32 K at the time of 2.583 s corresponding to the injection current of 2.6 A. A critical facet temperature and a high photon flux can be regarded as the key precondition for the occurrence of COD [4,19], and their results indicated that the COD process of cw-operating high-power LDs is due to a thermal runaway process. Following the COD occurrence the crystal restructure damage is produced in the output facet and then propagates into the cavity, which was so-called dark line defect (DLD) [20].…”
mentioning
confidence: 97%
“…The threshold current densities and slope efficiencies is 0. 19 In our experiments, the temperature distribution images of the entire output facet of the LDs were obtained from an FLIR System SC5700 camera working in the 3.7-4.8 mm range images with a temperature resolution of 20 mK. The thermal infrared camera recorded the images with a frequency of 115 Hz (1 ms integration time, 7.6 ms dead time) and a spatial resolution of about 3.0 mm per pixel.…”
mentioning
confidence: 99%
“…The actual limiting event can take one of a number of forms such as catastrophic optical damage [3][4][5] or spatial hole burning [6][7][8]. The general approach to raising these limits is to design a heterostructure which effectively confines high power in the lasing mode while maintaining low internal optical intensities.…”
Section: Introductionmentioning
confidence: 99%